Associations between cohort study participation and self-reported health and well-being: the Northern Finland Birth Cohort 1966 Study. Issue 12 (8th September 2022) - Taanila, Heli; Rönkä, Anna Reetta; Keinänen-Kiukaanniemi, Sirkka; Jokelainen, Jari; Nordström, Tanja; Taanila, Anja; Hurtig, Tuula
Abstract : Aim: The aim of this study was to explore whether active participation in a longitudinal birth cohort study is associated with study participants' health behaviour and well-being. Methods: The subjects of this study were part of the Northern Finland Birth Cohort 1966. The follow-up data were collected through clinical examinations and questionnaires when the cohort members were 1, 14, 31 and 46 years old. In this study, cohort participation activity was divided into three categories: active, semiactive and least active. Results: The total number of study participants who participated in the 46-year follow-up on both the survey and clinical trials was 6392, of which 66.5% (n=4268) participated actively in the cohort study. A total of 67.6% were female (p<0.001). Of the participants, 23.7% (n=1519) were semiactive and 9.5% (n=605) were the least active. Women who participated least actively experienced statistically significantly more depressive symptoms and poorer health, were more dissatisfied with their lives and had more addiction problems. In men, there was not a statistically significant association between participation activity and these well-being variables other than addiction problems and mental health. Conclusions: The findings indicate that participation activity is associated with better self-reported health and well-being, especially among women. With this knowledge, people can be encouraged to participate in longitudinal health research and, at the same time, may improve their own health and quality of life.